The ditch : [large type] / a novel - Koch, Herman, 1953- (Thorndike Press Large Print Core, 2019)
When Robert Walter, popular mayor of Amsterdam, sees his wife toss her head back with laughter while chatting to one of his aldermen at a New Year's reception, he immediately suspects the worst. Despite their long and happy marriage, Robert is convinced that Sylvia is cheating on him--with the respectable alderman who is dedicated to the environment, no less. The man who wants to spoil the capital's skyline with wind turbines. The New Year's reception marks the end of the "happy family" era that the mayor has enjoyed for so long. His wife and their daughter, Diana, however, are not aware of his suspicions and carry on as usual. Robert starts spending a lot of time and energy "behaving normally." Naturally, his normal behavior is far more suspicious. Normally Robert's not really present when he's at home--he's preoccupied with his phone, the newspapers, and his own thoughts. But now Robert is so sure he'll miss the clues if he doesn't pay attention that he starts to be almost alarmingly attentive and interested--ultimately losing himself in increasingly panicked and paranoid trains of thought.